A high-capacity lead-acid battery positive electrode additive and a method for preparing modified lead paste

Through a microcapsule bag, the triangular dioxide technology is used to increase the 4BS content and pore rate of the positive electrode of the lead -acid battery, solve the problem of low energy density of lead -acid batteries and early capacity loss, and significantly extend the cycle life of the battery.

CN118888757BActive Publication Date: 2025-01-24ZHEJIANG EDENDA NEW ENERGY MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411354321.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-24
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The discharge capacity of the positive electrode plate of the lead-acid battery is lower than that of the negative electrode plate, resulting in low energy density, and serious problems in early capacity loss and softening and shedding of active substances, affecting the battery cycle life.

Method used

Use microcapsule technology to embed tritenux dioxide, prepare cases of chitosan-sodium alginate-starch microcapsules to wrap the tritenux dioxide additive. Through the formula of modified lead paste, increase the 4BS content and pore rate in the lead paste, enhance the skeleton skeleton Structure, avoid the effect of "no effect".

Benefits of technology

It significantly increased the 4BS ratio in the lead paste, enhanced the osteter structure and pore rate of the active substances, extended the cycle life of the battery, and solved the problem of early capacity loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118888757B_ABST
    Figure CN118888757B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lead-acid battery production, and in particular to a method for preparing a high-capacity lead-acid battery positive electrode additive and a modified lead paste. Antimony trioxide is embedded in chitosan-sodium alginate-starch microcapsules to prepare an antimony trioxide additive. Lead paste raw materials include lead powder, 4BS crystal seeds, dilute sulfuric acid, deionized water, short fibers and antimony trioxide embedded in microcapsules. Antimony trioxide is embedded in microcapsules to prepare an antimony trioxide additive embedded in sodium alginate-chitosan-starch microcapsules. The additive can not only reduce the inhibitory effect of antimony trioxide on 4BS synthesis, but also increase the 4BS content in the lead paste, which is beneficial to increasing the porosity of the lead paste and enhancing the skeleton structure of the lead paste, and the battery can avoid the influence of an "antimony-free effect" during charging and discharging through a "slow release" mechanism, thereby effectively improving the discharge capacity and cycle life of the lead-acid battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lead-acid battery production, and in particular to an additive for a positive electrode of a high-capacity lead-acid battery and a method for preparing a modified lead paste. Background Art

[0002] Lead-acid batteries are one of the most mature and widely used energy storage batteries, but their market competitiveness is gradually declining due to their low energy density. At present, the discharge capacity of the positive plate of lead-acid batteries is much lower than that of the negative plate. Therefore, improving the utilization rate of the active material (PAM) on the positive side is the key to improving the energy density of lead-acid batteries. In essence, the utilization rate of PAM is limited by factors such as ion / electron transport characteristics, interface structure, active site density involved in electrochemical reactions, contact area with electrolyte, and ion diffusion distance. In particular, the interface corrosion layer connecting PAM and the grid is usually a high-impedance lead oxide layer, which makes the lead-acid battery prone to early capacity loss (PCL) and rapid failure. In addition, PAM continues to expand and shrink in volume during the charging and discharging process, which makes the bonding between PAM and PAM and the grid worse, resulting in softening and shedding of PAM, and ultimately shortening the cycle life of the battery.

[0003] The existing technology attempts to solve the above technical problems by adding additives and optimizing the lead paste formula. For example, CN107317027B discloses a lead paste for positive electrode of lead-acid battery with 4BS seed added. Due to the addition of tetrabasic lead sulfate (4BS) seed, the 4BS content and crystal size uniformity in the lead paste are increased, the PAM porosity is increased, and the PAM skeleton structure is enhanced, but the problem of "antimony-free effect" in the grid interface corrosion layer still exists.

[0004] For example, CN118486827A discloses a method for preparing positive electrode lead paste. By adding bismuth trioxide and silica sol, the contact between particles and agglomerates in the active material is enhanced, and the connection strength between the active material and the grid is improved, thereby slowing down the softening and shedding of the active material.

[0005] For another example, CN107331862B discloses a method for preparing a deep cycle battery lead paste that is conducive to the generation of 4BS. Antimony trioxide and stannous sulfate additives that inhibit the synthesis of 4BS are added in two acid additions to form a lead paste containing 4BS. Although the influence of the "antimony-free effect" on early capacity loss is avoided, the proportion of 4BS in the lead paste component is less than 18%, and the advantages of 4BS are not fully utilized. Therefore, there is an urgent need for a solution to improve the comprehensive performance of the positive electrode of lead-acid batteries. Summary of the invention

[0006] In view of the low energy density of lead-acid batteries and the limitations of the prior art, the purpose of the present invention is to provide a positive electrode additive for a high-capacity lead-acid battery. Antimony trioxide is embedded in the microencapsulation technology to obtain an additive of sodium alginate-chitosan-starch microcapsules encapsulating antimony trioxide, which can not only reduce the inhibitory effect of antimony trioxide on 4BS synthesis, but also increase the 4BS content in the lead paste, which is beneficial to increase the porosity of the lead paste and enhance the skeleton structure of the lead paste, and through the "slow release" mechanism, the battery avoids the influence of the "antimony-free effect" during the charging and discharging process, thereby effectively improving the discharge capacity and cycle life of the lead-acid battery.

[0007] To achieve the above purpose, the present invention specifically adopts the following technical solutions:

[0008] The invention provides a positive electrode additive for a high-capacity lead-acid battery. Antimony trioxide is embedded in the antimony trioxide by adopting microcapsule technology to prepare a chitosan-sodium alginate-starch microcapsule-encapsulated antimony trioxide additive.

[0009] In the present invention, in the chitosan-sodium alginate-starch microcapsule encapsulating antimony trioxide additive, the preparation technology of the chitosan-sodium alginate-starch microcapsule coating layer is particularly critical, requiring the coating layer to have a certain degree of mechanical rigidity, softness and acid dissolution resistance, so as to prevent the release of antimony ions from antimony trioxide during the preparation and curing of the lead paste, and to meet the characteristics of being able to be dissolved during battery formation and charging and discharging, so as to achieve the dual effects of increasing the 4BS ratio of the lead paste and solving the problem of early capacity loss.

[0010] The production method of chitosan-sodium alginate-starch microcapsules encapsulating antimony trioxide comprises the following steps in sequence:

[0011] Step S1, taking a certain volume of chitosan solution and calcium chloride solution, mixing them, adjusting the pH value to 2-6, placing them in a glass container, and stirring them magnetically at room temperature with the speed controlled at 200-600 r / min, which is recorded as liquid A;

[0012] Step S2, mixing a certain amount of antimony trioxide with the starch dispersion and stirring for 30-60 minutes to form a uniform dispersion of antimony trioxide adsorbed by starch, which is recorded as liquid B;

[0013] Step S3, mixing solution B with the sodium alginate solution, stirring magnetically at a constant temperature, and controlling the rotation speed to 200-600 r / min, which is recorded as solution C;

[0014] Step S4, dripping liquid C into liquid A at a certain rate with a needle, slowly stirring for 10-20 minutes after dripping, then standing for 10-15 minutes, filtering to separate the colloid particles and washing with water, and finally vacuum drying to obtain a chitosan-sodium alginate-starch microcapsule-embedded antimony trioxide product.

[0015] In the present invention, the encapsulation rate, encapsulation layer thickness and product particle size of the chitosan-sodium alginate-starch microcapsules encapsulating antimony trioxide are closely related to the synthesis conditions. For example, if the chitosan concentration is too high, the collision probability between the wall materials will increase and the microcapsules will agglomerate. If the concentration is too low, it will not be enough to form a coating layer, which will reduce the encapsulation rate. For example, the size of the microemulsion droplets of the intermediate state of antimony trioxide encapsulated by sodium alginate-starch and the speed of the droplet acceleration rate also jointly determine the size, uniformity and encapsulation rate of the microcapsules. Therefore, in order to achieve the purpose and effect of the present invention, it is necessary to strictly control the preparation technical conditions.

[0016] A further preferred technical solution is that in step S1, the concentration of the chitosan solution is 10-50 g / L, the concentration of the calcium chloride solution is 10-30 g / L, acetic acid and sodium hydroxide solution are used for adjustment, and the stirring speed is 300-500 r / min; in step S2, the antimony trioxide particle size is 0.5-5 μm, the antimony trioxide concentration in liquid B is 50-120 g / L, the starch concentration is 20-50 g / L, and the stirring time is 30-50 min; in step S3, the constant temperature is 30-60° C., and the stirring speed is 300-500 r / min; in step S4, the nozzle diameter of the needle is 20-50 μm, and the dripping rate is 1-5 mL / min. When the nozzle diameter specification of the needle changes, the dripping rate also changes accordingly.

[0017] The starch includes but is not limited to wheat starch, corn starch, potato starch, cassava starch, etc., because it has abundant hydroxyl groups and porous structure, it is a good adsorbent and can adsorb antimony trioxide inorganic matter to form a coated core.

[0018] The starch in the coating inner layer can be interconnected with the sodium alginate through physical adsorption and hydrogen bonding, and serves as a growth prototype to facilitate the subsequent formation of microcapsules.

[0019] The chitosan is a natural high molecular weight straight chain alkaline polysaccharide, which has cationic properties due to a large number of primary amine groups on its molecular chain, while sodium alginate has a large number of carboxyl groups on its molecular chain. The two can be assembled into a multi-layer microcapsule shell through positive and negative charge attraction under electrostatic force, thereby enhancing the protective effect on the antimony trioxide core.

[0020] A further preferred technical solution is that in step S1, the concentration of the chitosan solution is 15-45 g / L, the concentration of the calcium chloride solution is 15-30 g / L, and the pH value is 4.5-5.2; in step S2, the antimony trioxide particle size is 1-3 μm, the antimony trioxide concentration in liquid B is 60-80 g / L, and the starch concentration is 30-40 g / L; in step S3, the constant temperature is 40-45°C; in step S4, the nozzle diameter of the needle is 50 μm, and the dripping rate is 1-3 mL / min.

[0021] In addition, the present invention also provides a method for preparing a lead paste modified by using the above-mentioned positive electrode additive for a high-capacity lead-acid battery, which comprises the following steps in sequence:

[0022] Step T1, first add the lead powder, 4BS seed crystals, short fibers and chitosan-sodium alginate-starch microcapsules to a paste mixer, and perform dry mixing to obtain a dry powder;

[0023] Step T2, adding the deionized water and dilute sulfuric acid to the dry material in sequence, performing a wet mixing operation, and obtaining a lead paste intermediate;

[0024] Step T3, stirring the lead paste intermediate and cooling it while stirring to obtain a final modified lead paste product.

[0025] A further preferred technical solution is that in step T1, the dry mixing operation time is 5-10 minutes; in step T2, the addition time of the dilute sulfuric acid and deionized water is ≤0.5 minutes, and the wet mixing operation time is 8-12 minutes.

[0026] A further preferred technical solution is that in step T3, the cooling rate of the cooling operation is ≤5°C / min, and the stirring operation is completed before the temperature of the lead paste intermediate drops to 55°C.

[0027] The beneficial effects of the present invention are:

[0028] (1) In the conventional power battery formula, the present invention adopts microcapsule technology to prepare sodium alginate-chitosan-starch microcapsules to encapsulate antimony trioxide additives to replace uncoated antimony trioxide. The microcapsule coating layer reduces the release of antimony ions in the lead paste and during the preparation and curing of antimony trioxide by physical barrier and metal-hydroxyl complexation. As a result, the influence of antimony trioxide on the nucleation and growth process of 4BS crystals is effectively reduced, and the 4BS ratio of the lead paste is significantly increased.

[0029] (2) The 4BS lead paste containing antimony trioxide of the present invention strengthens the skeleton structure of the active material and improves the porosity of the active material, which is beneficial to increase the reaction area of ​​the active material and accelerate the ion diffusion rate during the electrochemical reaction;

[0030] (3) During the operation of the battery, the microcapsules of the present invention gradually release antimony trioxide, which not only improves the conductivity of the corrosion layer at the interface between the grid and the active material and greatly increases the interface charge transfer rate, but also forms an antimony gel compound, which helps to increase the area of ​​the PAM gel region and the thickness of the amorphous material, thereby reducing the content of electrochemically inert crystalline reaction substances, ultimately greatly improving the discharge capacity of the battery and solving the problem of early capacity loss during charging and discharging.

[0031] In summary, the sodium alginate-chitosan-starch microcapsule encapsulated antimony trioxide additive of the present invention can effectively improve the comprehensive performance of the positive electrode of the lead-acid battery and extend the service life of the battery, and is particularly suitable for the technical field of positive electrode additives for lead-acid energy storage batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a scanning electron microscope image of the positive electrode additive of the present invention;

[0033] Figure 2 The XRD pattern of the lead paste obtained in Example 1 is shown below;

[0034] Figure 3 The XRD pattern of the lead paste obtained in Example 2;

[0035] Figure 4 This is the XRD pattern of the lead paste obtained in Example 3. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0038] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0039] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail in combination with the embodiments below. The antimony trioxide additive coated with the microcapsule technology prepared by the method of the present invention is compared with the unmodified version. The lead paste formula is the same, and the weight ratio is 100 parts of lead powder, 1 part of 4BS seed, 0.1 part of antimony trioxide, 0.1 part of short fiber, 8 parts of sulfuric acid (acid specific gravity is 1.4g / mL), and 12 parts of deionized water. The preparation steps of the lead paste are as follows: add lead powder, 4BS seed, modified or unmodified antimony trioxide, and short fiber to the paste machine, dry mix and stir for 5 minutes; then add water within 1 minute, and stir for another 5 minutes; then add acid, and the total time of acid addition is controlled to be completed within 12 minutes, and the highest temperature does not exceed 80°C, and stir for 5 minutes, and cool to less than 50°C to obtain the lead paste.

[0040] Embodiment 1:

[0041] A positive electrode additive for high-capacity lead-acid batteries, antimony trioxide is embedded in chitosan-sodium alginate-starch microcapsules to prepare antimony trioxide additives, scanning electron microscope images are attached Figure 1 .

[0042] The production method of chitosan-sodium alginate-starch microcapsules encapsulating antimony trioxide comprises the following steps in sequence:

[0043] Step S1, taking 0.1 L of 15 g / L chitosan solution and 0.1 L of 15 g / L calcium chloride solution, mixing them, adjusting the pH value to 4.5, placing them in a glass container, and stirring them magnetically at room temperature at a speed of 300 r / min, and recording them as liquid A;

[0044] Step S2, 8 g of antimony trioxide with a particle size of 3 μm and 0.1 L of 40 g / L starch dispersion were mixed and stirred for 30 min to form a uniform dispersion of antimony trioxide adsorbed by starch, which was recorded as liquid B;

[0045] Step S3, mixing solution B with the sodium alginate solution, stirring with a magnetic force at 40° C., and controlling the rotation speed to 300 r / min, which is recorded as solution C;

[0046] Step S4, dripping liquid C into liquid A at a rate of 5 mL / min using a needle with a pore size of 50 μm, slowly stirring for 20 min after dripping, then standing for 15 min, filtering to separate the colloid particles and washing with water, and finally vacuum drying to obtain a chitosan-sodium alginate-starch microcapsule-embedded antimony trioxide product with an embedding rate of 90%.

[0047] The chitosan-sodium alginate-starch microcapsule-embedded antimony trioxide product with a lower embedding rate was mixed with lead powder, 4BS seed crystals, short fibers, deionized water, and sulfuric acid according to the above method to prepare a lead paste. After the lead paste was solidified, the 4BS content in the lead paste was determined by XRD. The XRD diagram is shown in the attached Figure 2 The composition results of the lead paste are shown in Table 1.

[0048] The lead paste prepared by the above method was coated on the board and cured, and a 2V4Ah lead-acid battery was made according to the conventional process. The battery cycle charge and discharge test rules are as follows: constant voltage 2.4667V, current limit 2A charging for 4.25 hours, discharge at 2A current to 1.75V, when the discharge time reaches 96 minutes, it is regarded as the condition for the end of battery life. The battery cycle test results are shown in Table 2.

[0049] Embodiment 2:

[0050] A positive electrode additive for high-capacity lead-acid batteries is prepared by embedding antimony trioxide with microcapsule technology to obtain chitosan-sodium alginate-starch microcapsules encapsulating antimony trioxide additives.

[0051] The production method of chitosan-sodium alginate-starch microcapsules encapsulating antimony trioxide comprises the following steps in sequence:

[0052] Step S1, taking 0.1 L of 25 g / L chitosan solution and 0.1 L of 20 g / L calcium chloride solution, mixing them, adjusting the pH value to 5.2, placing them in a glass container, and stirring them magnetically at room temperature at a speed of 300 r / min, and recording them as liquid A;

[0053] Step S2, 6 g of antimony trioxide with a particle size of 2 μm and 0.1 L of 30 g / L starch dispersion were mixed and stirred for 30 min to form a uniform dispersion of antimony trioxide adsorbed by starch, which was recorded as liquid B;

[0054] Step S3, mixing solution B with the sodium alginate solution, stirring with a magnetic force at 40° C., and controlling the rotation speed to 300 r / min, which is recorded as solution C;

[0055] Step S4, dripping liquid C into liquid A at a rate of 3 mL / min using a needle with a pore size of 50 μm, slowly stirring for 10 min after dripping, then standing for 10 min, filtering to separate the colloid particles and washing with water, and finally vacuum drying to obtain a chitosan-sodium alginate-starch microcapsule-embedded antimony trioxide product with an embedding rate of 95%.

[0056] The chitosan-sodium alginate-starch microcapsule-embedded antimony trioxide product with a high embedding rate was mixed with lead powder, 4BS seed crystals, short fibers, deionized water, and sulfuric acid according to the above method to prepare a lead paste. After the lead paste was solidified, the 4BS content in the lead paste was determined by XRD. The XRD diagram is shown in the attached Figure 3 The composition results of the lead paste are shown in Table 1.

[0057] The lead paste prepared by the above method was coated on the board and cured, and a 2V4Ah lead-acid battery was made according to the conventional process. The battery cycle charge and discharge test rules are as follows: constant voltage 2.4667V, current limit 2A charging for 4.25 hours, discharge at 2A current to 1.75V, when the discharge time reaches 96 minutes, it is regarded as the condition for the end of battery life. The battery cycle test results are shown in Table 2.

[0058] Embodiment 3:

[0059] A positive electrode additive for high-capacity lead-acid batteries is prepared by embedding antimony trioxide with microcapsule technology to obtain chitosan-sodium alginate-starch microcapsules encapsulating antimony trioxide additives.

[0060] The production method of chitosan-sodium alginate-starch microcapsules encapsulating antimony trioxide comprises the following steps in sequence:

[0061] S1, take 0.1 L of 45 g / L chitosan solution and 0.1 L of 30 g / L calcium chloride solution, mix them, adjust the pH value to 5.0, place them in a glass container, stir them magnetically at room temperature, and rotate at 400 r / min, record them as A solution;

[0062] S2, 10 g of antimony trioxide with a particle size of 1 μm and 0.1 L of 30 g / L starch dispersion were mixed and stirred for 30 min to form a uniform dispersion of antimony trioxide adsorbed by starch, which was recorded as liquid B;

[0063] S3, mix solution B with sodium alginate solution, stir magnetically at 45°C, and control the speed to 400 r / min, which is called solution C;

[0064] S4. Liquid C was dripped into liquid A at a rate of 1 mL / min using a needle with a pore size of 50 μm. After dripping, the mixture was slowly stirred for 12 minutes, and then allowed to stand for 15 minutes. The colloid particles were separated by filtration and washed with water. Finally, the mixture was vacuum dried to obtain a chitosan-sodium alginate-starch microcapsule-encapsulated antimony trioxide product with an embedding rate of 97%.

[0065] The chitosan-sodium alginate-starch microcapsule-embedded antimony trioxide product with a high embedding rate was mixed with lead powder, 4BS seed crystals, short fibers, deionized water, and sulfuric acid according to the above method to prepare a lead paste. After the lead paste was solidified, the 4BS content in the lead paste was determined by XRD. The XRD diagram is shown in the attached Figure 4 The composition results of the lead paste are shown in Table 1.

[0066] The lead paste prepared by the above method was coated on the board and cured, and a 2V4Ah lead-acid battery was made according to the conventional process. The battery cycle charge and discharge test rules are as follows: constant voltage 2.4667V, current limit 2A charging for 4.25 hours, discharge at 2A current to 1.75V, when the discharge time reaches 96 minutes, it is regarded as the condition for the end of battery life. The battery cycle test results are shown in Table 2.

[0067] Comparative Example 1:

[0068] Unmodified antimony trioxide was mixed with lead powder, 4BS seed crystals, short fibers, deionized water, and sulfuric acid according to the above method to prepare lead paste, which was then coated on the board and cured. A 2V4Ah lead-acid battery was made according to the conventional process. The battery cycle charge and discharge test rules are as follows: constant voltage 2.4667V, current limit 2A charging for 4.25 hours, discharge at 2A current to 1.75V, and when the discharge time reaches 96 minutes, it is used as the condition for the end of battery life. The battery cycle test results are shown in Table 2.

[0069] Comparative Example 2:

[0070] Lead powder, 4BS seed crystal, short fiber, deionized water and sulfuric acid were prepared into lead paste according to the above method, and coated on the board and cured, and a 2V4Ah lead-acid battery was made according to the conventional process. The charging and discharging test rules of the battery cycle are as follows: constant voltage 2.4667V, current limit 2A charging for 4.25 hours, discharge to 1.75V with 2A current, and when the discharge time reaches 96 minutes, it is regarded as the condition for the end of battery life. The battery cycle test results are shown in Table 2.

[0071] Table 1 Comparison of the content of each component in lead paste determined by XRD

[0072]

[0073] Table 2 Comparison of battery test results

[0074]

[0075] From the test results of the above batteries, it can be seen that the initial room temperature capacity of Examples 1, 2, 3 and Comparative Example 2 of the present invention is higher than that of Comparative Example 1, which is increased by 2.2%, 11.2%, 7.2% and 7.9% respectively, which is related to the 4BS content; the battery cycle life of Examples 1, 2 and 3 of the present invention is significantly improved compared with Comparative Examples 1 and 2, especially the cycle life of Example 2 is 43.8% higher than that of Comparative Example 1 and 6.4 times that of Comparative Example 2. The above results fully demonstrate the beneficial effects of the products of the present invention in improving the utilization rate of lead paste, increasing battery capacity and cycle life.

[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A positive electrode additive for a high-capacity lead-acid battery, characterized in that: Antimony trioxide is embedded by microcapsule technology to prepare chitosan-sodium alginate-starch microcapsules encapsulating antimony trioxide additives; The method for producing chitosan-sodium alginate-starch microcapsules encapsulating antimony trioxide additive comprises the following steps in sequence: Step S1, mixing a chitosan solution and a calcium chloride solution, adjusting the pH value to 4.5-5.2, placing in a glass container, and magnetically stirring at room temperature, controlling the speed to 200-600 r / min, recorded as liquid A, the chitosan solution concentration is 15-45 g / L, the calcium chloride solution concentration is 15-30 g / L, and the pH value is adjusted with acetic acid and sodium hydroxide solution; Step S2, mixing antimony trioxide and starch dispersion for 30-60 min to form a uniform dispersion of antimony trioxide adsorbed by starch, which is referred to as liquid B, wherein the particle size of antimony trioxide is 1-3 μm, the concentration of antimony trioxide in liquid B is 60-80 g / L, and the concentration of starch is 30-40 g / L; Step S3, mixing solution B with the sodium alginate solution, stirring with magnetic force at a constant temperature of 40-45° C., and controlling the rotation speed to 300-400 r / min, which is recorded as solution C; Step S4, dripping liquid C into liquid A at a constant speed with a needle, the nozzle diameter of the needle is 50 μm, the dripping rate is 1-5 mL / min, stirring for 12-20 min after dripping, and then standing for 10-15 min, filtering and separating the colloid particles and washing with water, and vacuum drying to obtain a chitosan-sodium alginate-starch microcapsule-embedded antimony trioxide product, and the embedding rate of antimony trioxide additive is 90%-97%.

2. A method for preparing a lead paste modified with a positive electrode additive for a high-capacity lead-acid battery according to claim 1, characterized in that: The following steps are involved: Step T1, adding lead powder, 4BS seed crystals, short fibers and chitosan-sodium alginate-starch microcapsules to a paste mixer in sequence, and performing dry mixing to obtain a dry powder; Step T2, adding deionized water and dilute sulfuric acid to the dry material obtained in step T1 in sequence, performing a wet mixing operation, and obtaining a lead paste intermediate; Step T3, stirring the lead paste intermediate obtained in step T2, and simultaneously performing a cooling operation to obtain a final modified lead paste product.

3. The method for preparing a modified lead paste according to claim 2, characterized in that: In step T1, the dry mixing operation time is 5-10 minutes; in step T2, the addition time of dilute sulfuric acid and deionized water is ≤0.5 minutes, the wet mixing operation time is 8-12 minutes, and in step T3, the cooling rate of the cooling operation is ≤5°C / min, and the stirring operation is completed before the temperature of the lead paste intermediate drops to 55°C.

Citation Information

Patent Citations

  • A lead paste for positive electrode of lead-acid batteries containing 4BS seed crystals

    CN107317027B

  • A method for preparing lead paste for deep-cycle batteries with 4BS (4-bit / 4-bit) properties

    CN107331862B

  • Lithium secondary battery containing capsule for controlled-release of additives

    CN101213703A

  • Tea polyphenol microcapsules with fixed-point release characteristics and application thereof

    CN107455754A

  • Modified lead paste for battery positive plate and preparation method of modified lead paste and positive plate

    CN118676317A